El régimen de transición, respecto de la naturaleza del traslado entre fondos de pensiones cuando ya se ha vencido el término legal para hacerlo (2018)
Many of those who save for their pension have no knowledge about what type of fund their money keeps. Moreover, many do not know that they have the option of deciding where to save. In Colombia, there is a few years ago the Multifondos scheme that, due to its novelty, does not provide a sufficient history to show the advantages of this scheme. However, cases such as Chile and Peru, which implemented this same scheme a few years ago, its behavior reflected in the figures has shown its benefits in the savings of members. The duty of information and pension advice on the part of the Administrating Entities of Pension Funds in Colombia EAFP to its affiliates and potential affiliates is fundamental in the General Pension System, for the pension rights and expectations that have to be acquired, and for the the very nature of informed consent that must be constituted based on respect for the principle of freedom of information that members of the system have. In the Colombian legal system, social security enjoys special protection since it is constituted as a fundamental right. In articles 48 and 49 of the Political Constitution of Colombia, social security is instituted in a dual way, that is; on the one hand, an inalienable right of all persons within the territory, and on the other hand, as a public service, which the State has the obligation to direct, coordinate and control its effective execution, in its main components Health, Pension and Risks Labor. The foregoing is strengthened and complemented by international instruments that recognize the right of people to social security, as established by the jurisprudence of the constitutional court in Sentence T 719 of 2011. In some cases, there were people who went to court to reverse their process, but to date, there are few judicial decisions of nullity of membership, applicable to persons outside the transition regime, in favor of those who at the time took the hasty and little analyzed decision to join the Individual Savings Scheme with Solidarity administered by private pension funds, attracted by arguments for which they sold dreams of a better future for old age. These are people who today suffer a harsh reality that compromises the right to a decent life of these people, who throughout their working life made a great effort accumulating the required quota as a contribution of the respective legal contributions to access an old-age pension, possibly under the life annuity method. They are people who, due to the incomprehension of the information provided by the sellers of private pension funds, as will be seen in the arguments of this article, whose projection, when compared to that offered in the Medium Premium Regime with Defined Benefit , it is harmful to the expectations of the worker with very significant differences, so that the monthly income of those who would be accessing an old-age pension with life annuity in the Individual Savings with Solidarity Scheme -RAIS- compared with the pension of Old age offered in the Medium Premium Regime with Defined Benefit –RPMPD- In this order of ideas, it is necessary and important to emphasize that the administrators have the obligation to protect the right to information that all people in the system have, always seeking to obtain the greatest clarity in the information regarding the conditions of said change and to provide knowledge not only of the favorable part of that regime but also of all that may be harmful to the event that a person decides to join or move. Finally, it is not enough that the AFPs generate the transfer to COLPENSIONES, it is also a matter of condemning the defendant to pay for the damages caused, which are evaluated in what would have to correspond to the average premium scheme with benefit defined Situation that was analyzed to be facing a nullity in the affiliation by the advisor in which the deception not only in what is affirmed but in what the advisor stops saying as generating a favorable decision for him and a detriment pension for the member.